Studi Tingkat Pemahaman Nilai-Nilai Agama Dalam Menghadapi Budaya Berpacaran Dikalangan Siswa - Pratiwi, Retno Ayu; Zulaikha, Siti Zulaikha; Wahyudi, Waluyo Erry (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
This study fills a research gap by showing that a strong religious understanding does not always lead adolescents to act morally in the context of digital culture. To address this gap, we conducted a qualitative case study at Tunas Dharma Junior High School, engaging 12 key informants through in-depth interviews, observations, questionnaires, and documentation. We applied thematic analysis to interpret the data. The results show that 88.6%–95.5% of students demonstrate very high levels of moral knowing (C2–C4 of Bloom's Taxonomy). However, students still engage in dating practices through intensive communication on social media, the use of alternative accounts, and covert interactions. Weak moral sentiments, a cognitive-normative educational approach, the distortion of religious teachings online, and limited environmental support contribute to this gap. Theoretically, this study strengthens a model of religious value internalization that integrates moral knowledge, moral feelings, and moral actions. Practically, the findings propose integrating religious digital literacy, strengthening intrinsic motivation, and applying contextual educational strategies to bridge the gap between students' religious knowledge and moral behavior. These findings can guide school policies and support the development of sustainable local curricula.